Liquefied microcapsules as dual-Mmcrocarriers for 3D+3D bottom-up tissue engineering - Correia, Clara R. (2020)
Cell encapsulation systems must ensure the diffusion of molecules to avoid the formation of necrotic cores. The architectural design of hydrogels, the gold standard tissue engineering strategy, is thus limited to a microsize range. To overcome such a limitation, liquefied microcapsules encapsulating cells and microparticles are proposed. Microcapsules with controlled sizes with average diameters of 608.5 ± 122.3 µm are produced at high rates by electrohydrodynamic atomization, and arginyl-glycyl-aspartic acid (RGD) domains are introduced in the multilayered membrane. While cells and microparticles interact toward the production of confined microaggregates, on the outside cell-mediated macroaggregates are formed due to the aggregation of microcapsules. The concept of simultaneous aggregation is herein termed as 3D+3D bottom-up tissue engineering. Microcapsules are cultured alone (microcapsule1 ) or on top of 2D cell beds composed of human umbilical vein endothelial cells (HUVECs) alone (microcapsule2 ) or cocultured with fibroblasts (microcapsule3 ). Microcapsules are able to support cell encapsulation shown by LiveDead, 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulphofenyl)-2H-tetrazolium (MTS), and dsDNA assays. Only microcapsule3 are able to form macroaggregates, as shown by F-actin immunofluorescence. The bioactive 3D system also presented alkaline phosphatase activity, thus allowing osteogenic differentiation. Upon implantation using the chick chorioallontoic membrane (CAM) model, microcapsules recruit a similar number of vessels with alike geometric parameters in comparison with CAMs supplemented with basic fibroblast growth factor (bFGF).